Investigating the impact of a 20 miles per hour speed limit intervention on road traffic collisions, casualties, speed and volume in Belfast, UK: 3 year follow-up outcomes of a natural experiment. Issue 1 (15th November 2022) - Hunter, Ruth F; Cleland, Claire L; Busby, John; Nightingale, Glenna; Kee, Frank; Williams, Andrew James; Kelly, Paul; Kelly, Michael P; Milton, Karen; Kokka, Kelly; Jepson, Ruth
Abstract : Background: Evidence regarding the effectiveness of 20 miles per hour (mph) speed limit interventions is limited, and rarely have long-term outcomes been assessed. We investigate the effect of a 20 mph speed limit intervention on road traffic collisions, casualties, speed and volume at 1 and 3 years post-implementation. Methods: An observational, repeated cross-sectional design was implemented, using routinely collected data for road traffic collisions, casualties, speed and volume. We evaluated difference-in-differences in collisions and casualties (intervention vs control) across three different time series and traffic speed and volume pre-implementation, at 1 and 3 years post-implementation. Results: Small reductions in road traffic collisions were observed at year 1 (3%; p=0.82) and year 3 post-implementation (15%; p=0.31) at the intervention site. Difference-in-differences analyses showed no statistically significant differences between the intervention and control sites over time for road traffic collisions. There were 16% (p=0.18) and 22% (p=0.06) reductions in casualty rates at years 1 and 3 post-implementation, respectively, at the intervention site. Results showed little change in mean traffic speed at year 1 (0.2 mph, 95% CI −0.3 to 2.4, p=0.14) and year 3 post-implementation (0.8, 95% CI −1.5 to 2.5, p=0.17). For traffic volume, a decrease in 57 vehicles per week was observed at year 1 (95% CI –162 to −14, p<0.00) and 71 vehicles at year 3 (95% CI −213 to 1, p=0.05) post-implementation. Conclusion: A 20 mph speed limit intervention implemented at city centre scale had little impact on long-term outcomes including road traffic collisions, casualties and speed, except for a reduction in traffic volume. Policymakers considering implementing 20 mph speed limit interventions should consider the fidelity, context and scale of implementation.